DETERMINATION OF THE INFLUENCE OF THE LENGTH OF THE TESTED YARN SAMPLES ON THEIR MECHANICAL CHARACTERISTICS - ABDUJABBAROV, MUSLIMBEK; ALIEVA, DILBAR; KARIMOV, RAKHIM (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This study investigates how yarn sample length affects its mechanical properties, specifically focusing on tensile strength and elongation under break. Using the YG026T tensile testing machine, yarn samples of varying lengths (200mm, 300mm, 400mm, and 500mm) were examined. Results indicated that shorter yarn samples exhibited higher relative breaking loads and elongation percentages compared to longer samples, which implies a significant relationship between sample length and breaking characteristics. These findings provide insights for optimizing weaving processes and adjusting parameters to enhance fabric quality.